Respon Pertumbuhan dan Hasil Padi (Oryza sativa L.) terhadap Cekaman Suhu Tinggi - Khamid, Miftakhul Bakhrir Rozaq; Junaedi, Ahmad; Lubis, Iskandar; Yamamoto, dan Yoshinori (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
Global climate change will imply to increase in atmospheric temperature, which can affect the sensitive stadia and decrease rice yield. The objective of this research was to study the growth and production of rice varieties under hightemperature stress. This research was conducted using a split-plot design under partitioned polyethylene house in order to create temperature differences among main-plots. The partitioned treatment successfully increased by 1.7 °C of average temperature with a maximum temperature of 35.0 °C (T1) and 37.6 °C (T2). Rice varieties, namely IR64, Ciherang, IPB-3S, Way Apo Buru, Jatiluhur, Menthik Wangi and Silugonggo were randomized as sub-plot. The results showed that increasing temperature had no significant effect on plant height, tiller number, SPAD-value, leaf area index, and crop growth rate, but significantly decreased 1,000 grains weight by 4.57% and harvest index by 20%. The interaction between temperature and varieties significantly affected a percentage of a productive tiller and partially filled spikelets. Ciherang variety produced the lowest percentage of productive tillers on T2 by 57.6%. Way Apo Buru variety produced the lowest percentage of partially filled spikelets on T2 by 3.01%.